Principles of Good Faith in Harmonization of Partnership Cooperation on the Distribution of Nine Food Ingredients at PT Sarana PanganMadani, Pekanbaru City - Yeni Triana; Handana (International Journal of Science, Technology & Management, 2021)
The problem of limited knowledge of partners about agreements or contracts in general, and in particular regarding the principle of good faith in business activities faced by business actors and company management, which generally consists of millennial youth, which can be said to be still lacking in understanding the principle of commitment well, as a guideline in carrying out the actions of a company, especially companies with legal entities, such as Limited Liability Companies, where PT Sarana PanganMadani, has established many partnerships, which of course must keep the relationship harmonious, sometimes the relationship is already running, due to limited knowledge, experience, there was a clash that would definitely hinder good relations, both parties, for example, at the beginning of the negotiation there was an agreement, which gave birth to a partnership to distribute the nine staples, but in its implementation, there were obstacles, which caused Due to the difference in prices, even though at the beginning of the negotiation the price was already agreed to, but there was a change, which was due to an increase in market prices or production prices, so that the price that was agreed upon earlier, of course changed, this change is a problem of misunderstanding between the two parties, according to Partners. PT Sarana PanganMadani, the company raised prices unilaterally, while from the PT stated that due to changes in market prices, this is one example which is a significant obstacle, resulting in inconsistencies in the development of partner businesses which are good business groups providing distribution of nine staples daily activities, as well as providing business capital to develop agricultural land, as well as services, ranging from basic materials to packaging ready to be marketed. In this community service program, the priority issue agreed upon by the PKM FH Unilak proposer together with his partner, PT Sarana PanganMadani, to be resolved is to provide understanding through legal counseling about the principles of good faith in cooperating with the business community. Thus, after the program is implemented, it is hoped that partners will gain a correct understanding and have knowledge of agreements or contracts in general, and in particular the principles of good faith in this partnership. The method that will be used in this community service is to use lectures that will be directly at the PT Sarana PanganMadani office.